1975
DOI: 10.1121/1.2002228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance study of several pitch detection algorithms

Abstract: A comparative performance study of seven pitch detection algorithms was conducted. A speech data base, consisting of eight utterances spoken by three males, three females, and one child was constructed. Telephone, close talking microphone, and wideband recordings were made of each of the utterances. For each of the utterances in the data base; a "standard" pitch contour was semiautomatically measured using a highly sophisticated interactive pitch detection program. The "standard" pitch contour was then compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Some of the raw analysis results for speaker Dl are presented in the M.S. thesis of Cheng [18]. Finally, because of the large number of factors involved in the analysis, each of the error measurements was averaged over the utterances of each speaker.…”
Section: B Results Oferroranalysismentioning
confidence: 99%
“…Some of the raw analysis results for speaker Dl are presented in the M.S. thesis of Cheng [18]. Finally, because of the large number of factors involved in the analysis, each of the error measurements was averaged over the utterances of each speaker.…”
Section: B Results Oferroranalysismentioning
confidence: 99%
“…The hardware pitch detector described in Section III has been built and interfaced to the NOVA computer facility of the Acoustics Research Department. An extensive performance evaluation was made of the capabilities of this and several other pitch-detection algorithms using software simulations [9]. To test the performance of these algorithms, a speech data base, consisting of eight utterances spoken by 3 males, 3 females, and 1 child was constructed.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…When the pitch period exceeds 150 samples, the analysis frame size is not large enough to hold two full periods of speech; thereby increasing the chance of a gross error in locating the correct pitch period. In the study of [9], the two low-pitch speakers used in the study both showed a large number of gross errors in the pitch period (for both the telephone and microphone recordings). All other speakers had only occassional gross errors in the pitch period (i.e., one gross error/s on average).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations